Bubblings of a Family of Singular Pseudo-holomorphic Disks (Journal of Partial Differential Equations, 2020)
In this paper we will discuss the bubblings at corners of a family of pseudo-holomorphic disks with their boundaries in a Lagrangian subvarieky with corners.
Keywords: Pseudo-holomorphic disk; bubbling; moduli space; corner